Spray-dried nanocrystal-loaded polymer microparticles for long-term release local therapies: an opportunity for poorly soluble drugs - Carlos Rodríguez-Nogales; Joke Meeus; Gaby Thonus; Sam Corveleyn; Eric Allémann; Olivier Jordan (Taylor & Francis Group, 2023)
AbstractNano- and micro-technologies can salvage drugs with very low solubility that were doomed to pre-clinical and clinical failure. A unique design approach to develop drug nanocrystals (NCs) loaded in extended release polymeric microparticles (MPs) for local treatments is presented here through the case of a potential osteoarthritis (OA) drug candidate for intra-articular (IA) administration. Optimizing a low-shear wet milling process allowed the production of NCs that can be subsequently freeze-dried (FD) and redispersed in a hydrophobic polymer-organic solvent solution to form spray-dried MPs. Results demonstrated a successful development of a ready-to-upscale formulation containing PLGA MPs with high drug NC encapsulation rates that showed a continuous and controlled drug release profile over four months. The screenings and procedures described allowed for identifying and overcoming common difficulties and challenges raised along the drug reduction to nano-size and spray-drying process. Above all, the technical knowledge acquired is intended for formulation scientists aiming to improve the therapeutic perspectives of poorly soluble drugs.